IN VITRO STUDIES ON CALCIUM OXALATE CRYSTAL GROWTH INHIBITION OF STROBILANTHES CRISPUS EXTRACTS - Afrizal Itam; Zhari Ismail; Amin Malik Shah Abdul Majid (Universitas Andalas, 2009)
ABSTRACT Strobilanthes crispus L. (Acanthaceae) has been used locally in traditional medicine for kidney stone and related diseases. These plant extracts have the ability to inhibit the calcium oxalate crystal growth, where the ability of water extract is higher than those of the 70% acetone, methanol and acetone extracts. The ability to inhibit the calcium oxalate crystal growth of these extracts is lower than that of sodium citrate as positive control. Keywords: Strobilanthes crispus, Acanthaceae, crystal inhibition, calcium oxalate